TEMUAN TERAKOTA DARI SITUS BOJONG GANDU, KERTABUMI, CIAMIS: SEBUAH TELAAH BENTUK DAN RAGAM HIAS 1 - Endang Widyastuti (Kemendikbud, 2018)
In a study that conducted in the Kertabumi area, terracotta artifacts were found with unique shapes and decorations. The terracottas were found in a considerable amount. There are numerous variations in the shape and decoration of these findings. Locals refer to these artifacts as “kue”. The purpose of this paper is to classify these findings based on the shapes and decorative motifs. According to the grouping that has been done it is known that there are 4 groups based on the cross section; there are rectangular, semicircular, elliptical and trapezoidal cross sections. Meanwhile the decoration on terracotta is in the form of lines, woven bamboo patterns, and circles. These decorations can appear together in one terracotta, while another terracotta only have one decoration.